Chicago [videorecording (DVD)] - Richards, Martin; Condon, Bill, 1955-; Marshall, Rob; Zellweger, Renée, 1969-; Zeta-Jones, Catherine, 1969-; Gere, Richard, 1949-; Queen Latifah, 1970-; Reilly, John C., 1965-; Liu, Lucy, 1968-; Beebe, Dion; Kander, John; Ebb, Fred; et al. (Miramax collector's series., 2005)
At a time when crimes of passion result in celebrity headlines, nightclub sensation Velma Kelly and spotlight-seeking Roxie Hart both find themselves on Chicago's famed Murderess Row. They also share Billy Flynn, the town's slickest lawyer with a talent for turning notorious defendants into local legends.